In vitro elucidation of antioxidant, antiproliferative, and apoptotic potential of yeast-derived β-1,3-glucan particles against cervical cancer cells - Upadhyay, Tarun Kumar; Trivedi, Rashmi; Khan, Fahad; Al-Keridis, Lamya Ahmed; Pandey, Pratibha; Sharangi, Amit Baran; Alshammari, Nawaf; Abdullah, Nadiya M.; Yadav, Dharmendra Kumar; Saeed, Mohd (Frontiers in Oncology, 2022)
Cancer is the leading root of mortality worldwide in which cervical cancer in particular is the fourth most common cause of mortality of women each year. Conventional treatments of cancer are chemotherapy and radiation therapy having various kinds of side effects. Hence, there is a high need to develop alternative efficient and safer therapies for cancer treatment. β- Glucan, a novel polysaccharide isolated from baker’s yeast Saccharomyces cerevisiae, shows noteworthy cytotoxicity towards a variety of cancer cell lines in vitro. In this research, we characterized the β-Glucan with HPTLC analysis and found that D-glucose units with β-1,3 links are the major component of the extracted β- Glucan particles. FTIR analysis confirmed a β-(1→3) linked Glucan structure. In vitro cell cytotoxicity was evaluated by MTT with IC50 136 μg/ml and therapeutic potential was assessed by various assays using values below and above the IC50.A significant ROS generation at 50-150μg/ml concentrations indicated the apoptosis of cervical cancer cells. Along with ROS generation, these concentrations were also found to induce morphological changes such as fragmentation in DNA upon staining HeLa cells with DAPI. Mitochondrial membrane potential was significantly reduced after increasing the dose of treatment, assessed by the help of MitoTracker dye. So, by all these experimental supports, we observed that β-Glucan have the potential to slow down the growth of cervical cancer cells and it can be further investigated for unfolding its complete anticancerous potential.